Geological steering technology for directional drilling of deep CBM horizontal wells in Qinshui Basin - WANG Yuhong, SUN Tianyu, LI Peng (Meikuang Anquan, 2023)
The geological structure of the deep coal seam in Qinshui Basin is relatively complex, which poses a new challenge to the control of the directional landing site of the horizontal well and the control of the drilling trajectory of the horizontal section, and the traditional methods based on the geological characteristics data and lithology of the target layer obtained by the guide hole drilling exploration are difficult to meet the precise trajectory control in the actual directional drilling process, and the requirements of drilling along the layer cannot be realized. In order to solve the problem of horizontal directional drilling control of deep wells, a set of geological guidance technology suitable for horizontal directional drilling of deep coalbed methane was proposed. The geological structure of the target coal seam was judged by early resonance analysis, the target formation parameters were obtained by the design and construction guide hole, and the drilling work was completed by using precise landing technology and horizontal section geological guidance technology. The technology was tested and applied in WXN-T27-L1 well in south Wuxiang block of Qinshui Basin, with a drilling horizontal section length of 708.00 m and a coal seam drilling rate of 85.51%, which significantly improved the coal seam drilling rate and shortened the drilling cycle.